Economics of Wheat Cultivation Under Different Sizes of Farms in Borunda Tubewell Command Area ( Rajasthan) - Vyas, D L; Kalla, Jagdeesh C (Annals of Arid Zone, 2016)
The data on costs an.d returns of production of wheat on 24 farm families in Borunda Tubewell Command area (1972-73) were analysed to explore the relationship between economics of wheat production and size of farm. The data conclusively revealed the better use of inputs like seeds, fertilizer and water on small farms as compared to medium and large farms. The analysis of efficiency of factors of production of wheat per hectare on different size of farm indicated that whereas labour and material use on small farms was most efficient, the role of fixed investment was more efficient in case of big farmers. From this study it could be conclusively established that for reducing imbalances of intra-farm variations in production of wheat, gradual but bold attempt of injecting capital to the small farmers will be quanon non of development programme in areas where irrigation has only recently been made available.